Dental Anxiety among Medical and Paramedical Undergraduate Students of Malaysia. (28th February 2017) - Gunjal, Shilpa; Pateel, Deepak Gowda Sadashivappa; Parkar, Sujal
Abstract : Aim . To assess the dental anxiety level among dental, medical, and pharmacy students of MAHSA University, Malaysia. Materials and Methods . A cross-sectional questionnaire study was conducted among 1500 undergraduate students of MAHSA University. The Modified Dental Anxiety Scale (MDAS) was used to measure dental anxiety among the study population. The responses were assessed by 5-point likert scale ranging from 1 to 5. The level of anxiety was categorized into lowly anxious (5–11), moderately anxious (12–18), and severely anxious ≥19. Out of 1500 students enrolled, 1024 students (342 males and 682 females) completed and returned the questionnaire having response rate of 68.26%. Results . There was a statistically significant difference (P < 0.001 ) when the mean dental anxiety scores were compared among the three faculties and dental students had lowest mean score (11.95 ± 4.21). The fifth year (senior) dental students scored significantly (P = 0.02 ) lower mean anxiety score as compared to the first dental students (junior). The students were anxious mostly about tooth drilling and local anesthetic injection. Conclusions . Dental students have a significantly low level of dental anxiety as compared with medical and pharmacy students. Incorporation of dental health education in preuniversity and other nondental university curriculums may reduce dental anxiety among the students.